LANGUAGE CURRICULUM DEVELOPMENT: A NEED ANALYSIS OF ENGLISH FOR ENGINEERING STUDENTS IN ORDER TO DEVELOP AN ESP (ENGLISH FOR SPECIAL PURPOSE) FOR ENGINEERING STUDENTS - Arianto, Yopi (Universitas Nusantara PGRI Kediri, 2016)
ABSTRACTEnglish is a language that used in various working fields. It makes English give various aspects to teach. For this reason, English for the students of University should be taught as what they need from English. With assumption that the students have learnt English for more than six years before Entering the University, English would be more meaningful and useful for them if they studied English referred to what faculty they are in. ESP is an option for the students as stated by Ibbotson (2010) “It (ESP) is designed to improve the communication skills and specialist to language knowledge to engineers, enabling them to work confidently and effectively”. ESP leads the students to learn what they need from English. As a result, they can learn two things: first, the English itself and the second is new knowledge about engineering. The point of ESP is to link between English and the specialization of the knowledge. Based on this reason, the study is conducted to find what the students need from English then the result is used as the pole in arranging an ESP curriculum. The data is obtained by interviewing the first semester engineering faculty students of Kahuripan University of Kediri. The data were analyzed qualitatively. The result indicates that most of the students need to learn English that support them at work (ESP), some students feel that they need to learn general English to reduce the lacking, some want to study the combination of general English and ESP. The conclusion from the research describes that the students with lacking in English needs to learn the Basic English before they learn ESP. In other side, the students argue that they realize the necessity of learning English but they want to have an ESP program with their level of English mastery. For short, the engineering students require themselves to take the benefit of learning ESP to support them at work. The ESP curriculum is arranged based on their necessities, lacks, and wants. Key Words: Curriculum, ESP (English for Specific Purpose), Engineering